Determination of Cloud Storage and IT Infrastructure on File Security - Wasserbauer, Michal (Dinasti International Journal of Digital Business Management, 2023)
This study discusses the determination of cloud storage and IT infrastructure for file security. The purpose of this study is to find out whether the application of cloud storage plays a role in securing files and implementing IT infrastructure plays a role in securing files. The research method used is descriptive qualitative, which aims to obtain hypotheses for further research. The results of this study include: 1) Cloud storage plays a role in securing files, where by implementing and using cloud storage, companies can more easily access cloud computing. So that it does not require disk space on hardware and 2) IT infrastructure plays a role in securing files, where with adequate IT infrastructure such as: network, hardware and software it will make it easier for companies to secure files. Other IT infrastructure that can be done is in the form of developing the speed of the company's internet network, in addition to making it easier for company employees to convey information. High internet speed is also useful in transferring and securing files and backing up files. If one of the company's hardware is attacked by a virus, the data can be quickly transferred with high internet speed. Another infrastructure is the development of its own applications, so that companies can easily control and operate applications according to the wishes and needs of the company. There are other factors that affect file security, including: 1) Employee performance; 2) Employee education; and 3) Competitive advantage.